Oralité, littérature et didactique : quelles convergences disciplinaires ? - Corinne Weber (Corela)
This contribution aims to reflect on the place of literature from the early 20th century, that oralised the narrative voice. The question will be asked whether such corpora are adapted to teach or learn to pronounce the French language. It is assumed that corpora from the spoken word literature provide an interesting data bank as a tool for cultural and linguistic mediation, at the service of variations in pronunciation. Examples will illustrate our point. This interdisciplinary perspective, between phonetics, didactics and literature, aims to establish a dialogue that will ensure that the gap between literature and language is overcome.